2023
DOI: 10.1038/s41598-023-34182-z
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of electroacupuncture on intestinal barrier lesions in IBS and UC model

Abstract: Irritable bowel syndrome (IBS) and ulcerative colitis (UC) are two intestinal diseases with different pathological changes. Electroacupuncture (EA) at Zusanli (ST36) on both IBS and UC is widely used in clinic practice. But it is unclear whether acupuncture at one acupoint can treat two different intestinal diseases at different layers of intestinal barrier. To address this question, we explored three intestinal barrier lesions in IBS and UC mice with the aid of transcriptome data analysis and studied the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Some scholars have suggested that changes in goblet cell secretion in IBS can disrupt the intestinal chemical barrier. 33 , 37 We verified and obtained results showing a decrease in MUC2 expression in goblet cell secretion in IBS model. In comparison to IBS group, following TXYF treatment, the expression of MUC2 in goblet cells increased.…”
Section: Discussionsupporting
confidence: 67%
“…Some scholars have suggested that changes in goblet cell secretion in IBS can disrupt the intestinal chemical barrier. 33 , 37 We verified and obtained results showing a decrease in MUC2 expression in goblet cell secretion in IBS model. In comparison to IBS group, following TXYF treatment, the expression of MUC2 in goblet cells increased.…”
Section: Discussionsupporting
confidence: 67%
“…After 5 days of UC modeling, mice in the DSS + EA group were treated with EA once a day for 5 days ( 19 ). A custom-made mouse frame was used to hold the animals and both of the Zusanli acupoint points (ST36, located ~3 mm below the capitulum fibulae) were targeted by EA for 30 minutes (2 Hz, 0.2 mA) ( 20 ), the hind limbs of the mice began to tremble slightly. Similarly, the control and the DSS groups were held for 30 minutes without EA intervention.…”
Section: Methodsmentioning
confidence: 99%